Seasonal Variations in Soil Enzyme Activity and Nutrient Limitations of Differently Aged Pinus massoniana Plantation - Huiling Chen; Mengmeng Gou; Jianwen Hu; Lei Lei; Sufeng Zhu; Ruyuan Hu; Haiping Zhao; Wenfa Xiao; Changfu Liu (Microorganisms)
Soil extracellular enzymes (SEEs) affect the decomposition of organic matter and microbial nutrient demand. However, the seasonal dynamics of SEE activity for differently aged plantations is still unclear. To analyze the seasonal variations of SEE activity and nutrient limitation for differently aged plantations, this study employed the “space-for-time substitution” method and Pinus massoniana plantations of varying ages (6, 13, 29, 38, and 57 years) in subtropical China to determine SEE activity and nutrient limitations in the growing and non-growing seasons. The results showed that SEE activity varied notably with the growth stage and season. In particular, β-1,4-glucosidase activity was higher in the growing season than in the non-growing season, while the opposite was observed for acid phosphatase and leucine-amino-peptidase activity. Acid phosphatase gradually increased with stand age, peaking in the 38-year plantation for the growing and non-growing seasons. Microbial carbon (C)-limitation was higher in the growing season and gradually decreased with forest stand development. Phosphorus (P)-limitation was higher in the growing season than in the non-growing season and was maximum in the 38-year plantation. Moreover, the physicochemical properties and microbial biomass explained the microbial C- and P-limitations, respectively. Compared to the non-growing season, the C- and P-limitations of different stand ages were stronger during the growing season, and the physicochemical properties and microbial biomass were important factors affecting their changes. The study reveals the balance status between soil microorganisms and nutrients in subtropical forest ecosystems and provides guidance for the development of afforestation strategies.